Competitiveness and structural change in Salatiga economy - Mohammad Rofiuddin (Indonesian Journal of Islamic Economics Research, 2019)
The era of globalization has forced all regions at an increasingly fierce and sharp level of competition, both directly and indirectly, both in the domestic and international markets. One approach to overcoming these challenges is through a regional development that refers to increasing regional competitiveness as the basis for regional growth. The purpose of this study was to determine the leading sectors and shift in the share of economic sectors in Salatiga. The analytical method used in this research is the Estaban Marquillas Shift-Share (SS) analysis. The results showed that the sectors that had competitive advantages and specialization were as follows: (i) 2013, namely Water Supply, Waste Management, Waste and Recycling, Construction, Wholesale and Retail Trade; Car and Motorcycle Repair, Transportation and Warehousing, and Real Estate; (ii) in 2017, namely the Provision of Accommodation and Food and Beverage, Corporate Services, and Educational Services. Besides that, in Salatiga City, it can be said that the economic structure has shifted, namely Agriculture, Forestry, and Fisheries; Processing industry; Electricity and Gas Procurement; Water Supply, Waste Management, Waste and Recycling; Construction; Wholesale and retail trade; Car and Motorcycle Repair; Transportation and Warehousing; Provision of Accommodation and Food and Drink; Real Estate; Company Services; Educational Services.